Perceived predation risk decreases movement and increases aggregation of Amazon milk frog (Anura, Hylidae) tadpoles throughout ontogeny - Casillas-Barragan, Isabel; Costa-Pereira, Raul [UNESP]; Cardoso Peixoto, Paulo Enrique (Springer, 2016)
In order to maximize escaping success, prey may change their predator avoidance behaviors according to their susceptibility. Morphological development during ontogeny may lead to different susceptibility to predators. Consequently, prey may exhibit different predator avoidance strategies according to the ontogenetic state. In this study, we used tadpoles of the Amazon milk frog Trachycephalus resinifictrix (Anura, Hylidae) to evaluate how variation in the ability to actively escape owed to the mobility acquired through ontogeny affects the adoption of predator avoidance strategies. We sampled tadpoles (N = 384) in temporary ponds and divided them in four consecutive developmental stages according to body size and mobility capacity. Subsequently, we measured their movement and spatial distribution when subjected to chemical cues of predators or control solutions. We found that they spent less time moving and increased spatial aggregation after receiving solutions with predator cues, independent of their developmental stage. These results indicate that the variation in escape capacity through larval ontogeny does not determine their antipredator strategy. Since tadpoles of T. resinifictrix typically grow in environments with reduced space for active escaping, such as tree holes and bromeliads, it may be that the ability to flee from predators is absent, even when this behavior increases the survival chances.
Keywords: Antipredator strategies; Amazon milk frog; Ontogenetic stages; Distribution; Chemical cues; Dilution effect